Structure of the Lining Epithelium of the Cauda Epididymis of the Golden Hamster - Beu, C. C. L.; Orsi, A. M. [UNESP]; Domeniconi, R. F. (Wiley-Blackwell Publishing, Inc, 2009)
The ductus epididymis has roles in the maturation and storage of spermatozoa. The main function of the cauda epididymis is the storage of spermatozoa; however, this region exerts other morphophysiological roles. So, this study was aimed at investigating structural features of the cauda epididymis epithelium, which could indicate roles other than the storage. The relative percentages of the cell types in the epithelium were 74.9, 6.9, 12.5 and 5.6% of principal, clear, basal and halo cells respectively. Large intercellular spaces were seen among the lateral plasmatic membranes of adjacent principal cells or among these cells and others cell types. These spaces were found to be filled with multivesicular bodies, myelin figures, scrolls and debris of membranes or flocculent dense material. Clear cells had the cytoplasms filled with lysosomes (3/4 of basal cytoplasm), and vacuoles and vesicles (1/4 of apical cytoplasm). The observations allowed us to infer that clear cells could act in the process of endocytosis and also in water transfer from the lumen to the interstitium through the epithelium compartment. Moreover, transcytosis may occur at the cauda epididymis of Golden hamster.